Faktor-Faktor yang Mempengaruhi Niat Mahasiswa Akuntansi Generasi Z untuk Mengikuti Ujian CPA: Studi Empiris pada Mahasiswa S1 Akuntansi Generasi Z Universitas di Kota Padang - Intan Permata Bunda; Vita Fitria Sari (Jurnal Eksplorasi Akuntansi, 2026)
This study aims to examine the effects of attitude, reference group, and perceived behavioral control on the intention of Generation Z accounting students to take the Certified Public Accountant (CPA) Examination. This study employs a quantitative research method, with data collected through a Google Form questionnaire, involving 248 undergraduate accounting students from Andalas University, Universitas Negeri Padang, Universitas Putra Indonesia “YPTK” Padang, Universitas Bung Hatta, Universitas Muhammadiyah Sumatera Barat, Universitas Dharma Andalas, and Universitas Ekasakti. The respondents were selected using random sampling. The results indicate that attitude has a positive effect on the intention to take the CPA Examination, while reference group and perceived behavioral control do not have a significant effect. These findings suggest that the intention of Generation Z accounting students to pursue the CPA Examination is primarily driven by personal evaluation of the benefits and perceived importance of CPA certification, rather than social influence or beliefs regarding the ease or ability to access and complete the examination.